The effects of corporate social responsibility (CSR) on organizational performance - Muhumuza Noah. M (UCU, 2024)
This study examined the effects of corporate social responsibility on organizational performance, with a focus on Coca-Cola company in Namanve. The study focused on how the practiced corporate social responsibility affected its performance. The target population was comprised of 50 workers, whereas a sample of 44 respondents was selected using Tora Yamane's method. Data was collected via questionnaires, and the results were analyzed using SPSS software. The analysis reveals that CSR is perceived as having a substantial positive impact on organizational performance, particularly in areas related to public image, employee engagement, and profitability. However, the variability in responses for certain items highlights areas where the impact of CSR may be less uniformly experienced or understood. Furthermore, there is need to engage employees at all levels. Implementing corporate social responsibility requires the active engagement of employees at all levels within the organization. This can be done through encouraging employees to participate in CSR activities by providing them with opportunities to volunteer or contribute their skills towards relevant causes. There is also need for improving public image. People typically have a positive perception of collaborating with and for philanthropic businesses. Companies that implement corporate social responsibility (CSR) initiatives often enjoy favourable public images which can provide them with a competitive edge in the marketplace. Additionally, ensuring customer satisfaction and loyalty is essential. Customer satisfaction emerges from how customers perceive, assess, and emotionally respond to their experiences with a product or service. High levels of customer satisfaction can lead to behavioural outcomes, mutually beneficial relationship between the consumer and the provider.
Undergraduate dissertation